2017
DOI: 10.12973/ejmste/76958
|View full text |Cite
|
Sign up to set email alerts
|

Art and Geometry of Plants: Experience in Mathematical Modelling through Projects

Abstract: This article presents some results of a qualitative-case study carried out with students in last year of secondary education (15 -17 years) into an official educational institution. The research looked at learning outcomes through the development of mathematical modelling projects related to studying the distribution of the leaves and the growth of some plants. According to the results, when modelling projects grounded in studying the form and geometric magnitudes are carried out, students are able to find out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
3
0
3
Order By: Relevance
“…The analysis of the practice of project training described in a number of Russian and foreign articles [2]- [8], [10]- [39] (the list of published scientific papers related to the topic of the article is not complete and presents the most important and latest studies), has revealed the following advantages (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of the practice of project training described in a number of Russian and foreign articles [2]- [8], [10]- [39] (the list of published scientific papers related to the topic of the article is not complete and presents the most important and latest studies), has revealed the following advantages (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…N. Zapata-Grajales, N. A. Cano-Velásquez, J. A. Villa-Ochoa [39] offer a research project to study the shape and geometric quantities of plants based on mathematical modeling. This method is considered as a tool for the mathematization of natural objects.…”
Section: Resultsmentioning
confidence: 99%
“…The theoretical consideration as well as data analysis from this different contextual point of view is being reported for first time here. Zapata-Grajales et al, 2018). The latter, in particular, will be addressed in this article.…”
Section: Introductionmentioning
confidence: 91%
“…En ellos se observa un interés por reconocer la importancia de las situaciones de la cotidianidad y de la cultura como componentes determinantes en la producción de conocimiento por medio de la modelación matemática escolar (VILLA-OCHOA e LÓPEZ, 2011; VILLA-OCHOA e BERRÍO, 2015) este conocimiento no se subordina solo al conocimiento matemático, sino también al conocimiento que se involucra en los contextos, fenómenos y situaciones que se modelan. También existe un interés por reconocer procesos de modelación y la etnomatemática a través de prácticas de tallado en madera (AROCA, 2016), la articulación con el arte (ZAPATA-GRAJALES et al, 2018) (BORJA, 2017). En relación con la formación en arte, Zapata-Grajales y colaboradores observó que la reproducción de las formas de las plantas una herramienta propicia para producir conocimiento sobre las matemáticas, las plantas y el arte a través de la replicación.…”
Section: Modelación Como Medio Para Establecer Conexiones Con Los Conunclassified
“…En los últimos 20 años en Colombia ha habido un especial interés por la enseñanza de temas relacionados con el estudio del cálculo y otras áreas del análisis matemático a través de la variación(VILLA-OCHOA et al, 2018;MOLINA-TORO et al, 2018; PEÑA-PÁEZ e MORALES-GARCÍA, 2016; CRUZ e MEDINA, 2013), también el tema de sistemas de numeración, cantidades, medidas y magnitudes ha llamado la atención en modelación (AGUDELO e GARCÍA, 2016; ZAPATA-GRAJALES et al, 2018; RIVERA QUIROZ et al, 2018; TOLEDO-CHICAIZA e CRUZ-ROJAS 2018.). En este uso de la modelación como herramienta se puede establecer conexiones con otras herramientas, como por ejemplo las tecnologías digitales para la simulación (CRUZ e MEDINA, 2013; VILLA-OCHOA, et al, 2018; MOLINA-TORO et al, 2018, PEÑA-PAEZ e MORALES GARCIA, 2016) y para la visualización y la replicación de formas(ZAPATA- GRAJALES et al, 2018). Un elemento clave en estos trabajos radica en la autenticidad de los contextos usados; es decir, los autores se preocuparon para que los contextos usados para sus trabajos tuvieran cierta familiaridad y cercanía con los contextos e intereses de los estudiantes.…”
unclassified